1997
DOI: 10.1002/(sici)1097-4652(199705)171:2<205::aid-jcp11>3.0.co;2-c
|View full text |Cite
|
Sign up to set email alerts
|

Shear stress induction of the endothelial nitric oxide synthase gene is calcium-dependent but not calcium-activated

Abstract: Arterial levels of shear stress (25 dynes/cm2) can elevate constitutive endothelial nitric oxide synthase (eNOS) gene expression in cultured endothelial cells (Ranjan et al., 1995). By PhosphorImaging of Northern blots, we report that the eNOS/glyceraldehyde 3-phosphate dehydrogenase (GAPDH) messenger RNA (mRNA) ratio in bovine aortic endothelial cells (BAEC) increased by 4.8- and 7.95-fold after 6-hr shear stress exposure of 4 and 25 dynes/cm2, respectively. Incubation of BAEC with dexamethasone (1 microM) ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
26
0

Year Published

1999
1999
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 102 publications
(28 citation statements)
references
References 32 publications
2
26
0
Order By: Relevance
“…mitogen-activated protein kinases, and nuclear factor kappa B (NF-kB) in ECs (Berk et al, 1995;Couet et al, 1997;Jo et al, 1997;Ballermann et al, 1998;Traub and Berk, 1998). This subsequently stimulates eNOS mRNA expression (Uematsu et al, 1995;Harrison et al, 1996;Topper et al, 1996;Xiao et al, 1997;Malek et al, 1999;Chen et al, 2002) and/or augments NOS protein production (Chen et al, 2002) and the ability of ECs to release NO (Nishida et al, 1992;Noris et al, 1995;Guzman et al, 1997;Ito et al, 1997). Together with our earlier finding that IPCinduced vasodilation in the uncompressed muscle is magnified by a rapid inflation of IPC (Liu et al, 1999a, b), our findings suggest that IPC-mediated shear stress is a major mechanical factor in the stimulation of NO release from ECs, thereby inducing vasodilation in the uncompressed skeletal muscle.…”
Section: Effects Of Ipc On Enos Expressionsupporting
confidence: 76%
See 1 more Smart Citation
“…mitogen-activated protein kinases, and nuclear factor kappa B (NF-kB) in ECs (Berk et al, 1995;Couet et al, 1997;Jo et al, 1997;Ballermann et al, 1998;Traub and Berk, 1998). This subsequently stimulates eNOS mRNA expression (Uematsu et al, 1995;Harrison et al, 1996;Topper et al, 1996;Xiao et al, 1997;Malek et al, 1999;Chen et al, 2002) and/or augments NOS protein production (Chen et al, 2002) and the ability of ECs to release NO (Nishida et al, 1992;Noris et al, 1995;Guzman et al, 1997;Ito et al, 1997). Together with our earlier finding that IPCinduced vasodilation in the uncompressed muscle is magnified by a rapid inflation of IPC (Liu et al, 1999a, b), our findings suggest that IPC-mediated shear stress is a major mechanical factor in the stimulation of NO release from ECs, thereby inducing vasodilation in the uncompressed skeletal muscle.…”
Section: Effects Of Ipc On Enos Expressionsupporting
confidence: 76%
“…Shear stress is a potent and rapid inducer of the eNOS mRNA (Xiao et al, 1997;Ziegler et al, 1998). Blood flow alternation creates three primary mechanical forces on the ECs: shear stress, pressure, and tension (Traub and Berk, 1998).…”
Section: Effects Of Ipc On Enos Expressionmentioning
confidence: 99%
“…The genes chosen had all been shown to be sensitive to shear stress in vitro at the mRNA and/or protein level in a variety of endothelial cell types. 2,8,15,16,18,19,22,23,26 Consistent with the global tendencies revealed by microarray analysis, qPCR also showed that positive and negative deviations from moderate levels of shear stress were associated with similar gene expression responses. Among the seven genes studied by qPCR, the expression levels of four of them (b-catenin, c-jun, VCAM-1, and MCP-1) were altered in both the low shear and high shear environments relative to the medium shear environment (Fig.…”
Section: Discussionsupporting
confidence: 64%
“…The upregulation of eNOS mRNA in bovine aortic endothelial cells in vitro was found to be dose-dependent between 1.2 and 15 dyn/ cm 2 at 3 h, 23 and between 4 and 25 dyn/cm 2 at 6 h. 26 However, these exposures were of rather short duration. Following exposure of cultured porcine aortic endothelial cells to shear stresses ranging from 6 to 48 dyn/cm 2 for 24 h, we found a slight dependence (ln fold difference = 0.5 over shear range) of eNOS gene expression on shear stress level 11 ; between shear stresses of 12-48 dyn/cm 2 , there was no significant effect of shear on eNOS expression.…”
Section: Discussionmentioning
confidence: 91%
“…Over the next 4 to 8 h, any further increase in shear stress does not necessarily elicit a second Ca 2+ transient nor reactivate NF-κB (Ayajiki et al 1996). Moreover, a number of changes take place; one good example is an increase in the expression of eNOS (Nishida et al 1992;Xiao et al 1997;Ziegler et al 1998), and the increased production of NO from cells exposed to shear stress then counteracts the activation of NF-κB and, as a consequence, adhesion molecule and chemokine expression (Zeiher et al 1995;Shyy et al 1994a;Tsao et al 1995). Therefore, to avoid a generalized stress response, we preconditioned endothelial cells with a low shear stress for 16 h before increasing shear stress for an additional 4 h. Given the aforementioned effects on endothelial NO production, we expected that the activation of several signaling pathways by increasing the fluid shear stress applied to preconditioned endothelial cells would be less pronounced than that detected in statically cultured cells exposed to shear stress for a short period.…”
Section: Discussionmentioning
confidence: 99%